Scientific show: way to scientific literacy in schools municipal Maracanaú (Research, Society and Development, 2020)
This article substantiates the design and trajectory of the Scientific Shows of the Municipal Schools of Maracanaú, as a training space and an important contribution for the dissemination of the sciences, triggering actions to encourage the development of scientific works, expression of creativity, contributing to the development of skills of students, teachers and schools from research projects. Methodologically, it was used bibliographical research and documentary analysis. It is, therefore, a predominantly qualitative approach. The results reveal that the dissemination of Science through the projects of scientific initiation developed in Maracanaú, reached spaces beyond the Municipality itself, extrapolating the walls of the school through the approval of its projects in the most diverse state, national and international scientific shows. It was also verified that this event has contributed in the formative process of the teachers, causing them to rethink their pedagogical practices, making the school floor more reflective, awakening in the student the taste for research.